Legal Guarantees for the Right to Obtain Birth Certificates for Children in Orphanages: Jaminan Hukum Terhadap Hak Memperoleh Akta Kelahiran Bagi Anak Panti Asuhan - Arlianti Imaria Simanjutak (Unnes Law Journal, 2012)
Every children birth without any exception must have birth evidence as their first step to have a citizen identity. This research attepted to analyze the legal status of children who stay under institute care; To know the procedure of birth registration; To know the birth registration renstrains; and To know the civil and citixenship bureaucracy efforts in tackling the birth registrations renstrains. This research used qualitative approach. The result of the research reveals that mostly the children’s in the Institute have the birth certificate. They were registered through formal procedure in the Civil and Cintizenship Bureucrat. Some renstrains in the birth registratioan are regulation, administrative, and technical problem. Some efforts were taken by the Bureucrat and Institue as well are to make the procedure easier by cutting some administrative requirements.